2019
DOI: 10.1016/j.biopsycho.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Seeing myself through my heart: Cortical processing of a single heartbeat speeds up self-face recognition

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
(75 reference statements)
2
18
0
Order By: Relevance
“…We argue that the present findings about the coupling between breathing and self-other voice discrimination may reflect that voice perception and the voluntary action of speaking are coupled with the basic physiological function of breathing, which are absent (or less pronounced) for cardiac physiology. We also did not observe cardiac-dependent differences in reaction times as it has been reported for self-face perception (Ambrosini et al, 2019), arguing that different physiological signals (e.g. respiration and heartbeat) affect self-related processes differently, depending on their intrinsic cyclic differences, their specific functional associations, and likely the investigated sensory modality.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We argue that the present findings about the coupling between breathing and self-other voice discrimination may reflect that voice perception and the voluntary action of speaking are coupled with the basic physiological function of breathing, which are absent (or less pronounced) for cardiac physiology. We also did not observe cardiac-dependent differences in reaction times as it has been reported for self-face perception (Ambrosini et al, 2019), arguing that different physiological signals (e.g. respiration and heartbeat) affect self-related processes differently, depending on their intrinsic cyclic differences, their specific functional associations, and likely the investigated sensory modality.…”
Section: Discussionsupporting
confidence: 73%
“…We investigated whether self-voice perception would differ in trials occurring during different parts of respiratory (inspiration, expiration) and heartbeat (systole, diastole) cycles. Following previously reported breathing effects on cognition (Nakamura et al, 2018;Perl et al, 2019;Zelano et al, 2016) and heartbeat effects on self-face perception (Ambrosini et al, 2019), we predicted better performance in auditory tasks during inspiration and during systole. Additionally, we explored the effects of BSC modulations on respiration and cardiac phase dependency in self-voice perception.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…At systole, during a heartbeat, arterial baroreceptors signal to the brain, but at diastole, between heartbeats, this pathway is silent. Recent studies have shown that presentation of stimuli at systole decreases memory for words (Garfinkel et al, 2013) amplifies threat processing to fearful faces (Garfinkel et al, 2014) increases the expression of fear-related racial stereotyping (Azevedo, Garfinkel, Critchley, & Tsakiris, 2017) and speeds up self-face recognition (Ambrosini, Finotti, Azevedo, Tsakiris, & Ferri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A pertinent question that has engaged the attention of several researchers investigating self-face processing is the reason for this processing advantage ( Ma & Han, 2010 ; Wang et al., 2011 ). Several factors have been pointed out in previous research, for instance, a better structural encoding of self-face ( Keyes & Brady, 2010 ; Keyes et al., 2010 ; Qian et al., 2017 ), a greater familiarity with self-face ( Bortolon et al., 2018 ; Sui et al., 2006 ), or a multimodal representation of self-face ( Ambrosini et al., 2019 ; Apps et al., 2015 ; Northoff, 2011 ; Thirioux et al., 2016 ). Although many studies, including a recent meta-review ( Bortolon & Raffard, 2018 ), observe a significant advantage in identifying self-face, the stage at which self-face affects perceptual processing is not clearly understood.…”
mentioning
confidence: 99%